Composite bridge girders with corrugated steel web – A closer perspective - Ramanjaneyulu, K.; Kanchanadevi, A. (Journal of Structural Engineering, 2024)
Prestressed concrete composite girders with concrete flanges and corrugated steel web are being widely used for construction of bridges all over the world owing to their suitability for wide ranging bridge deck systems, such as girder-slab bridges, continuous bridges, box-girders, extra dosed and cable stayed bridges. The composite girder with corrugated steel web possesses several advantages, such as lightweight, prestressing efficiency, aestheticalappearance, suitability for earthquake prone areas and economy. These type of bridge girders are relatively new to India and guidelines for their design are yet to be codified. In this paper, different parameters which would aid in the design of composite girders with corrugated steel web are discussed. Further, details of innovative embedded shear connection developed for concrete flanges-steel web connection of composite girders are also presented. The load-slip responses of composite girders with embedded shear connections for different depths of embedment and varying dowel reinforcements are discussed. The importance of design equation proposed for predicting the shear resistance of the embedded shear connection is highlighted. Studies reported on performance of composite girders with corrugated web are also presented briefly to put forward the merits of these systems for adoption.